2006
DOI: 10.1063/1.2392995
|View full text |Cite
|
Sign up to set email alerts
|

Optical susceptibilities of supported indium tin oxide thin films

Abstract: The third-order nonlinear optical susceptibility of indium tin oxide ͑ITO͒ thin films on glass substrates, ͑3͒ ITO , was determined in the near-IR spectral region using degenerate four wave mixing ͑DFWM͒ spectroscopy with 100 fs laser pulses. A DFWM method for measuring thin films on thick substrates was refined for the characterization of films less than 100 nm thick and applied to ϳ25 nm thick ITO films. It was found that ͑3͒ ITO is purely electronic at 900-1300 nm ͑11 000-7700 cm −1 ͒ and has a value of ͑2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…This is taken into account by increasing the Drude damping rate in the antenna, which has been shown the dominant nonlinearity for Au in the near infrared. [21,22] Previous studies of the Kerr nonlinearity in ITO [37] have identified a relation with a polarization due to free carriers, resulting in a positive real χ (3) . Compared to those earlier studies, our current work involves much higher carrier densities and concomitantly stronger contribution from plasmonic effects.…”
Section: Numerical Model Of Nonlinear Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is taken into account by increasing the Drude damping rate in the antenna, which has been shown the dominant nonlinearity for Au in the near infrared. [21,22] Previous studies of the Kerr nonlinearity in ITO [37] have identified a relation with a polarization due to free carriers, resulting in a positive real χ (3) . Compared to those earlier studies, our current work involves much higher carrier densities and concomitantly stronger contribution from plasmonic effects.…”
Section: Numerical Model Of Nonlinear Modulationmentioning
confidence: 99%
“…We note that this model produces a positive and real Kerr coefficient at frequencies above the bulk plasmon frequency, consistent with results from earlier studies. [37] The individual effects of the two types of nonlinearity are shown in Fig. 5c.…”
Section: Numerical Model Of Nonlinear Modulationmentioning
confidence: 99%
“…The dielectric linear dispersion of Au, and Cr (adhesion layer) was fitted within the spectral range 400 nm -2000 nm to tabulated data [30] with a multi-coefficient function (allowing a tolerance of 0.1 and enforcing passivity), whereas the lossless SiO 2 (semi-infinite substrate) and ITO linear property was modelled as a constant permittivity of 2.122 and 2.890, respectively [30,26] . [27,26] .…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In the frequency ranges investigated, ITO has a moderately large third order susceptibility which is comparable to that of Si or GaAs. The origin of the large third order nonlinear susceptibility of ITO [38][39][40] is due to delocalized electrons with large mobility, analogous to pi-electrons in polymers 39 . Schematics of the excitation geometry and optical setup are shown in Fig.…”
mentioning
confidence: 99%